Creating ourselves : African Americans and Hispanic Americans on popular culture and religious expression - Pinn, Anthony B.; Valentin, Benjamin (e-Duke books scholarly collection., 2009)
Analyzes the religious and theological significance of African-American and Hispanic-American popular culture, structured in part as a dialogue between scholars from both ethnic groups.